Picosecond snapshot imaging of electric fields induced on a cone guide target designed for fast ignition scenario. (3rd August 2022) - Shi, Binghe; Yogo, Akifumi; Okamoto, Kazuki; Golovin, Daniil; Mirfayzi, Seyed Reza; Morace, Alessio; Arikawa, Yasunobu; Yamanoi, Kohei; Abe, Yuki; Murakami, Masakatsu; Gu, Yanjun; Mima, Kunioki; et al.
Abstract : In this study, we experimentally evaluate the ion transportation through a cone guide target, which accelerates ions up to MeV energies via target normal sheath acceleration, and transports them onto the position of imploding fuel in the fast ignition scenario of nuclear fusion. We measured the electric and magnetic fields (EM-fields) induced by return current streaming along the cone wall by proton radiography, and we report that the EM-fields are predominantly induced within a temporal window up to 30 ps after the laser injection. The magnitude of the electric field is maximized around 13 ps, reaching $4.0× 10^{10} V\ m^{-1}$, when the magnetic field is below 200 T. The present scheme provides insights on the EM-fields evaluation in the time region that is difficult to treat with simulations due to the computing resources.